Hubungan Dukungan Suami Dengan Efikasi Diri Pada Ibu Hamil Usia Remaja Di Puskesmas Ranomuut - Arruansilomba, Putri Pratiwi; Kundre, Rina Margaretha; Rompas, Sefti (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Background. Teenage is a period of transition from childhood to maturity, a problem that often occurs in teenagers is teenage pregnancy. The prevalence of teenage pregnancies is still high, the problem that is usually experienced by pregnant teenagers are lack of efficacy, one of the things that affects efficacy is husband's support during pregnancy. Objective. This study aims to determine the relationship between husband's support and self-efficacy in teenage pregnant women at the Ranomuut Health Center. Method. This study used a quantitative method with a cross sectional approach. Sampling used the total sampling method with a sample of 37 teenage pregnant women, using a husband's support questionnaire and a mother's self-efficacy questionnaire. Results. The statistical test uses the Spearman test with a confidence level of 95% or α = 0.05, the value is r = 0.001 <α = 0.05 with a coefficient value = 0.525. Discussion. Husband's support has a relationship with self-efficacy in teenage pregnant women at the Ranomuut Health Center. Conclusion. There is a significant relationship between husband's support and self-efficacy in pregnant women at the Ranomuut Health Center. Suggestion. It is hoped that teenage pregnant women will further increase their confidence during pregnancy, then their husbands can provide good assistance. For future researchers, it is hoped that they can provide interventions to increase self-efficacy and good husband support for teenage pregnant women and their husbands at the Ranomuut Health Center in Manado City.